Granular Construction: Designed Particles for Macro‐Scale Architectural Structures. (July 2017) - Dierichs, Karola; Menges, Achim
Abstract : Designing the individual particles of granular materials defines novel material characteristics of the overall granular system. This opens up a range of possibilities for architectural applications that are fully reconfigurable as the particles are not bound to each other. Karola Dierichs and Achim Menges of the Institute for Computational Design (ICD) at the University of Stuttgart provide an overview of recent research conducted at the Institute in this field. Autonomous construction is integrated into these systems through using either extrinsic autonomous machines or intrinsic autonomous particles.